Inclusive Leadership and Job Performance: A Study of Blue-Collar Worker Perceptions - Larney, Ammaarah (School of Management Studies, 2025)
In South Africa, blue-collar workers typically operate in labour-intensive work environments where inclusive leadership behaviours are often not viewed as a value-adding tool and where employee willingness to contribute to organisational processes is low. All of which can negatively impact individual job performance. Although there is growing literature focussing on inclusive leadership as a critical driver of job performance, there is a scarcity of research understanding this relationship in a South African blue-collar worker context, where this group is considered the backbone of the country's economy. This research argues that understanding the perceptions and behaviours of this group can be worthwhile when addressing the challenges faced by this group and identifying performance-motivating factors. The primary aim of this study was to explore the impact of perceptions of inclusive leadership on the job performance of blue-collar workers utilising three dimensions for performance, including (1) task performance, (2) contextual performance and (3) counterproductive work behaviour. Further, the moderating effect of psychological safety on this relationship was explored to expand on existing literature. Data was collected using a sample of 122 employees from multiple industries using self-report questionnaires. Data was analysed using correlation analysis, regression analysis and moderation analysis. The study's results revealed that the perceived perceptions of inclusive leadership of a blue-collar worker in South Africa positively influenced an employee's contextual performance and decreased the counterproductive work behaviour exhibited by an employee. Further, contrary to earlier studies, the results indicated that inclusive leadership did not significantly correlate with task performance. Additionally, this study revealed that psychological safety significantly correlated with task and contextual performance, whereas there was no significant relationship between psychological safety and counterproductive work behaviours. Despite the significance of these findings, the results were less robust than in previously published research. Lastly, it was observed that psychological safety was not an effective moderator of the relationship between inclusive leadership and job performance. Although these results were inconsistent with previous studies, these findings contribute to the growing body of inclusive leadership literature in South Africa.